Global steel production in the first two decades of the 21st century: a period of economic fluctuations and attempts to control globalisation processes - Matykowski, Roman; Tobolska, Anna (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2021)
Based on World Steel Association statistical data, this study brings together changes in the geographical pattern of global steel production in the first two decades of the 21st century and its fluctuations during economic and social crises. The analysis indicates a strong concentration of production in several countries, and among them, China has become the leader in the last two decades. Since 2017, it has produced more than half of all steel globally, and in 2019 its annual production exceeded one billion tonnes. In 2020 the largest Chinese concern, China Baowu Group, ousted ArcelorMittal from its leading position in the ranking of the world’s largest steel concerns. Such an intense concentration of steel production in one country and the strategies of internal consolidation of Chinese steel producers are a clear signal that China is taking control of the global market for this raw material, essential for many economic sectors.